Income and asset poverty among pastoralists in northern Kenya - Mburu, Samuel; Sousa-Poza, Alfonso; Otterbach, Steffen; Mude, Andrew G. (University of Hohenheim, 2016)
The Kenyan drylands, which make up about 84% of Kenya's total land surface, support about 8 million Kenyans with animal husbandry as the main source of livelihood. The livestock subsector in these dry areas accounts for over 70% of local family income, as well as 10% of the country's gross domestic product (GDP) and 50% of its agricultural GDP (Government of Kenya, 2012). Yet despite this sector's significant contribution to the economy, these dryland areas, especially in northern Kenya, have been undermined by systematic marginalisation, poor infrastructure and services, and persistent community conflicts and raids. At the same time, the threats from persistent droughts have escalated, with Northern Kenya recording 28 major droughts in the past 100 years and 4 in just the last 10 years and given the changing global climate, this trend is likely to continue or even worsen. These recurrent droughts and lack of supporting infrastructure have resulted in increased loss of livestock, leading to income loss that has rendered the pastoralists vulnerable to poverty. In this study, we use five waves of household panel data collected in the Marsabit district of Northern Kenya, to analyse the patterns of livelihood sources and poverty among pastoralists in that area. We estimate income poverty using imputed household income relative to the adjusted poverty line and asset poverty using a regression-based asset index and tropical livestock units (TLU) per capita. Our results indicate that keeping livestock is still the pastoralists' main source of livelihood, although there is a notable trend of increasing livelihood diversification, especially among livestock-poor households. The majority of households (over 70%) are both income and livestock poor with few having escaped poverty within the five-year study period. Disaggregating income and asset poverty also reveals an increasing trend of both structurally poor and stochastically nonpoor households. Food aid plays only a minor role in alleviating poverty.